Imaging Comparison Between Chinese and Japanese Patients With Cervical Ossification of the Posterior Longitudinal Ligament. Issue 23 (1st December 2018) - Xiao, Bin; Nagoshi, Narihito; Takeuchi, Ayano; Mao, Jianping; Liu, Bo; Tian, Wei; Tsuji, Osahiko; Okada, Eijiro; Fujita, Nobuyuki; Yagi, Mitsuru; Nakamura, Masaya; Matsumoto, Morio; et al.
Abstract : Study Design: A retrospective study. Objective: To identify the radiographic differences between Chinese and Japanese patients with cervical ossification of the posterior longitudinal ligament (OPLL) using computed tomography (CT) and magnetic resonance imaging (MRI), and to compare the characteristics of OPLL between the two nationalities. Summary of Background Data: OPLL has a high prevalence in East Asia. However, the differences between Chinese and Japanese OPLL patients are poorly known. Methods: This was a retrospective study of Chinese (n = 300) and Japanese (n = 102) consecutive patients who received a diagnosis of cervical OPLL between January 2010 and December 2014. All patients underwent CT and MRI. The type and distribution of OPLL were determined. Spinal compression was assessed by MRI. OPLL type, distribution, comorbidity, and compression of the spinal cord were examined. The ossification index (OP-index) was used to evaluate the OPLL. Factors contributing to the OP-index were examined by multivariate analysis. Results: The Chinese patients were younger than the Japanese patients ( P < 0.0001), and there were more women among the Chinese patients ( P = 0.0002). The OP-index was higher among the Japanese patients (median, 5 vs. 4, P = 0.003). Among men, OPLL lesions were more frequent in the under 55-year-old Japanese at C7 ( P = 0.04), in the 55 to 64-year-old Japanese at C4, C5, and C6 (all P < 0.05), and in the over 64-year-old Japanese at C3/4 ( P = 0.01), compared with their Chinese counterparts. Among women, OPLL lesions were more frequent in the 55 to 64-year-old Japanese at C6 ( P = 0.04). The multivariate analysis showed that only age was independently associated with the OP-index (odds ratio [OR] = 1.023, 95% confidence interval [CI]: 1.002–1.045, P = 0.034). Conclusion: Japanese patients had a higher frequency of OPLL lesions at C5, C6, and C7. Age was independently associated with OPLL. Level of Evidence: 3